PENERAPAN PENDEKATAN PROSES DALAM MENINGKATKAN MUTU PENDIDIKAN BERBASIS DIGITAL : SEBUAH KAJIAN LITERATUR - Saifullah El Afrinuddin Zain, Hanif; Aris Ringgi Allo; Ramika Dila; Azainil; Laili Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation in education drives educational institutions to develop more adaptive, systematic, and sustainable quality management systems. One increasingly relevant approach is the process-based approach, a quality management approach that places processes at the core of educational quality control and improvement. This article aims to analyze the concept of the process approach in digital-based education, the effectiveness of its implementation, the main challenges faced by educational institutions, and the practical implications for the development of digital education quality management. This study utilizes a literature review method with a systematic literature review (SLR) approach, examining various studies related to quality assurance, Quality Management Systems (QMS), e-learning, digital transformation, quality audits, and continuous quality improvement (CQI). The findings indicate that the process approach can enhance the consistency of digital learning design, the effectiveness of quality assurance, the efficiency of data management and accreditation, as well as support continuous quality improvement. The integration of digital technologies such as Learning Management Systems (LMS), quality information systems, and online QMS strengthens documentation, auditability, and data-driven decision-making. Nevertheless, the implementation of a digital-based process approach still faces obstacles in the form of human resource readiness, organizational resistance, limited digital infrastructure, and the complexity of cross-unit coordination. This article asserts that the process approach in digital education is not merely an administrative mechanism, but rather a socio-technical system that integrates quality governance, digital transformation, and organizational culture within a framework of continuous improvement.